3PC-012 Management of non-administered chemotherapy preparation: an opportunity to minimise drug waste in oncology pharmacy. (24th March 2020) - El Assil, A; Adade, C; Issa, R; Bechar, H; Zedou, A; Fassi Fihri, A; Rahali, Y
Abstract : Background and importance: The non-administration of cytotoxic preparations contributes significantly to drug waste and costs in the centralised cytotoxic preparation units (CCPU). Monitoring and proper management of returns of preparations could reduce drug wastage. Aim and objectives: The aim of the study was to analyse the reasons for returns and quantify reused cytotoxic preparations before and after implementation of corrective measures. Material and methods: A prospective study was conducted at our hospital pharmacy at the National Institute of Oncology over two 8 month periods (January to August 2018, January to August 2019). Data on the reasons, content and fate of returns were collected and analysed. Results: At the end of the first period, 125 preparations corresponding to 90 prescriptions were returned. Absence of the patient was the most common reason (56%), followed by crystallisation of product (19%), mainly taxanes. Docetaxel was the most returned preparation (17.6%). The corrective measures taken were: optimisation of communication between the CCPU and clinical services, strict dilution of taxanes and etoposide in glass vials and updating of physicochemical and microbiological stability sheets for cytotoxics. During the two study periods, we found a similar number of returns (0.6%) corresponding to 15 851€ and 16 874 €. The absence of the patient, the most frequent reason in the two periods, decreased from 56% to 40%. Product crystallisation decreased considerably (19% vs 2%). The number of reassigned preparations increased from 2.4% to 7%. Reusing corresponded to 64€ and 2760€ for period 1 and period 2, respectively. Conclusion and relevance: This study found a high number of preparations returned due to crystallisation by taxanes via interactions containing content. Updating the stability data of the anticancer drugs used in our hospital based on recent international guidelines and follow-up of chemotherapy preparations had a significant impact on the reasons and cost of returns. Vigilance by pharmacists is required when validating prescriptions in order to minimise the avoidable causes of chemotherapy wastage and to make savings. References and/or acknowledgements: No conflict of interest.